The Role of Guidance and Counseling Teacher in Handling Students' Aggressive Behavior - Aminersi L. Babang; Maria Loban; Philia C. Octovianus (Institut Agama Kristen Negeri Kupang, 2022)
This study aims to determine the role of Guidance and Counseling teachers in handling with students who behave aggressively at SMPN 2 Kupang City.This type of research is descriptive qualitative, data collection through interview and documentation This type of research is descriptive qualitative, collecting data through interview and documentation techniques. The subjects were 5 guidance and counseling teachers. The results showed that the role of guidance and counseling teachers in dealing with students who behaved aggressively at SMPN 2 Kupang City were: guidance and counseling teachers provide as counselor, consultant and facilitator, agent of change, coordinator, counselor as assessor, and career development.